Financial Management of the Mosque as an Effort to Improve the Welfare of Halal Food MSME Actors Around Jogokariyan Mosque, Yogyakarta - Ahmad Sanjaya; Suhada Suhada (International Journal of Economics and Management Research, 2025)
The purpose of this research is to find out management of mosque financial management in increasing MSME Halal Food as well as supporting and inhibiting factors in improving the welfare of MSME Halal Food actors around the Jogokariyan Mosque , Yogyakarta. In research This the author uses the method of data collection with through observation, interview and documentation. And the library materials then analyze with written source guidelines and draw conclusions. From the results of this study the authors analyze that the financial management used by the mosque in an effort to increase the economic welfare of the congregation is by using planning, organizing, actuating and supervising. And for supporting and inhibiting factors using two factors, namely from internal factors and external factors. The implications of the findings of this study are. The management of the economic empowerment bureau must be consistent and responsible for what has become their responsibility from each division. It is necessary to have supervision and problem-solving measures for the issues faced by Halal Food MSME actors so that they can continuously sustain and grow their businesses. The management of the economic empowerment bureau pays attention to increasing the welfare of Halal Food MSMEs through the implementation of small-scale trading business activities.